Epidemiological and genetic analysis of a 2014 outbreak of hepatitis A in Japan. Issue 45 (9th November 2015) - Ishii, Koji; Kiyohara, Tomoko; Yoshizaki, Sayaka; Kawabata, Kunio; Kanayama, Atsuhiro; Yahata, Yuichiro; Takahashi, Takuri; Kinoshita, Hitomi; Saitou, Takehito; Sunagawa, Tomimasa; Oishi, Kazunori; Uema, Masashi; et al.
Highlights: Most of a hepatitis A outbreak reported in spring of 2014 in Japan was caused by a single strain distributed simultaneously throughout Japan. Abstract: Hepatitis A virus (HAV) is one of the most common causes of feces-transmitted acute hepatitis worldwide. In Japan, most of HAV infections have been sporadic cases and a relatively low number of cases (approximately 100–150) of acute hepatitis A were reported in 2012 and 2013. However, in 2014, 342 cases were reported as of week 22. In order to characterize the viral agents causing this outbreak, we collected stool or sera (and both for three case) from patients with hepatitis A from many regions throughout Japan and performed genotyping of the VP1/P2A regions of HAV. We then used a multiple-alignment algorithm to compare the nucleotide sequences with those of reference strains. Phylogenetic tree analyses revealed that the 159 HAV isolates were divided into three subgenotypes: IA (137 cases), IB (4 cases), and IIIA (18 cases). The most unique feature of this outbreak was that for most subgenotype IA cases (103 out of 137 IA cases) the sequences analyzed shared 100% homology. Interestingly, the peak week for these IA infections was almost the same nationwide, suggesting that the epidemic of hepatitis A caused by this subgenotype IA strain may have expanded from a single source possibly because of one food-borne or waterborne source that was distributed nationwide at once.